The Effect of the Read, Answer, Discuss, Explain, and Create (RADEC) Learning Model Assisted by SIPEMA on the Critical Thinking Skills of Fifth Grade Elementary School Students in the Respiratory System - Nafisa Alfazuri; Dewi Nilam Tyas (Postgraduate, University of Mataram, 2026)
This study aims to examine the effectiveness of the RADEC learning model assisted by SIPEMA, an Augmented Reality-based medium, in improving elementary school students’ critical thinking skills on the human respiratory system topic. A quasi-experimental design with a nonequivalent control group was employed, involving an experimental class using the RADEC model and a control class using the Discovery Learning model. Both groups were supported by SIPEMA to control the influence of learning media. Critical thinking skills were measured using pretest and posttest instruments. Data were analyzed using descriptive and non-parametric inferential statistics. The Shapiro–Wilk test indicated non-normal data distribution. Therefore, non-parametric tests (Wilcoxon and Mann–Whitney U) were applied. The results showed a significant improvement in both groups (p < 0.05). The median scores increased more substantially in the experimental class compared to the control class. The N-Gain score in the experimental class (0.66) was higher than in the control class (0.42). Furthermore, the Mann–Whitney U test revealed a significant difference between the two groups (p = 0.01). These findings indicate that the RADEC model assisted by SIPEMA is more effective than Discovery Learning in improving students’ critical thinking skills.